AIEgens assisted label free DNA supersandwich immunoassay for ultrasensitive α-fetoprotein detection. (August 2022) - Ou, Xiaowen; Dai, Jingman; Huang, Yiting; Xiong, Xiaoqin; Zheng, Zhi; Lou, Xiaoding; Xia, Fan
Abstract: The traditional enzyme-linked immunosorbent assay has been widely applied in the field of protein detection. Nevertheless, the detecting performance suffers from high background. Herein, we choose label free molecules of aggregation-induced emission (AIE) to design DNA supersandwich immunoassay (DSI) for ultrasensitive α-fetoprotein (AFP) detection. The silole-R, typical water soluble AIEgens (fluorogen with AIE feature) with positive charges, adsorbs on phosphate backbone of DSI by electrostatic attraction. In this way, the AIEgens DSI allows for ultrasensitive detecting AFP with low limit of detection (1.4 ng/mL). Moreover, the AIEgens DSI demonstrates a higher signal-to-background ratio (10.94) than fluorescein isothiocyanate (FITC) DSI (4.38). This AIEgens DSI provides a novel fluorescent enhanced analysis of trace AFP for cancer diagnose. Graphical abstract: Image, graphical abstract .